Remote sensing techniques in the search for ancient shipwrecks: how to distinguish a wreck from a rock in geophysical recordings - Sakellariou, D. (Bulletin of the Geological Society of Greece, 2007)
This paper presents the way conventional marine geophysical methods may be used with the highest efficiency for deep-water archaeological research, especially for the detection of ancient shipwrecks. Their use becomes all the more effective, when the principles of oceanography and marine geology are being followed during the interpretation of the geophysical recordings. The integration of sub-bottom profiling data provides valuable information on the geological structure of the seafloor ’s shallow substrate, which are an almost absolute prerequisite for a geologically reasonable interpretation of the side scan sonar images. Otherwise, interpretation of the sonar recordings may be erroneous or may be in direct discrepancy with the shallow sub-seafloor geological structure. Limitations of the efficiency of the geophysical methods in the case of targets of biogenic or anthropogenic origin or in shallow water environments are also being discussed